A construção do feminino nos romances A república dos sonhos e Vozes do deserto, de Nélida Piñon - Oliveira, Dileane Fagundes de (2022)
This research is part of a journey that started within the family, where I discovered the first feminist manifestations, and outlined in the course of my academic trajectory. The inquiries and conceptions regarding the social representations of the feminine have changed over the years, but some uncertainties persisted. Some of them guide the development of this thesis: what female representations populate the novels The Republic of dreams (1984) and Voices of the desert (2004), by Nélida Piñon? Questions and conceptions about the social representations of the feminine have changed over the years, but some concerns persisted. Some of them guide the development of this thesis: what female representations populate the novels The Republic of Dreams (1984) and Voices of the Desert (2004), by Nélida Piñon? How are they built, and how do they incite the reader, prompting him to rethink forms of social organization? From these questions, I discuss and analyze the writing of a woman about female characters, crossing with the ways of thinking about the feminine that circulate in our society. In order to contribute to the field of gender studies in literature, I present possibilities for reading the literary, through the scrutiny of female experiences and subjectivities built in this universe. At first, I present a synthesis of the life and work of the writer Nélida Piñon, demarcating her space in the Brazilian literary system. Once I start from a feminist reading of the narratives analyzed, I sought subsidies in the revision of the traditional worldview of the feminine through the rescue of the considerations of Simone de Beauvoir in The Second Sex , by Shulamith Firestone in The Dialectic of Sex and the Thomas Walter Laqueur in Making sex: Body and Gender from the Greeks to Freud . I also briefly review the main manifestations of feminism, its unfoldings and contribution to the various social spheres, especially in the literary scene. In addition, I reflect on issues related to female authorship and the constitution of the canon. I think of these perspectives from the reflections of Donna Haraway, Teresa de Lauretis, Judith Butler, Joan Scott, Elaine Showalter and Rita Terezinha Schmidt, among others. In the second part of the thesis, I seek to understand how the author constructs different female representations in the novels The republic of dreams (1984) and Voices of the desert (2004). In each of the narratives, I seek to investigate and understand the gender relations, the social practices, and the discourses that interfere in the construction of the characters. At last, I seek to present an intersection between the narratives, exposing the way Nélida Piñon articulates different modes of subjectivation of the feminine in each plot, seeking to investigate the movements of shifting and displacement of behavioral models crystallized by society.